(untitled) (Revista da Escola de Guerra Naval, 2023)
Since the 19th century, Latin America has progressively become a zone of peace. Between 1800 and 2007, the region has been affected by only fourteen inter-state wars. In addition, the frequency of inter-state wars has rapidly declined over the decades, generating a consolidated zone of peace. This paper examines the reasons behind regional peace in Latin America, reviewing the main theories of war and peace and assessing their validity in explaining the absence of inter-state wars in the region. The study finds that each one of the theories considered addresses only a single aspect of this phenomenon. Based on that, a multifaceted explanation of regional peace in Latin America is proposed, combining different theories to provide a more complete analysis of the phenomenon. This explanation presents peace in Latina America as the result of two interacting elements: countries’ satisfaction with their borders and the presence of weak states in the region. While recognizing that political regimes can influence countries’ war-proneness (and that democratic regimes tend to be less war-prone than authoritarian regimes), this study shows that democracy is not the ultimate cause of regional peace in Latin America. Indeed, the presence of authoritarian regimes in the region did not hinder the creation of a zone of peace between the 19th and 20th century. However, the study highlights that the spread of democracy in the region helped consolidating the zone of peace and determined its evolution from mere absence of war to institutionalized security community